A Randomized Trial of Maternal Docosahexaenoic Acid Supplementation to Reduce Inflammation in Extremely Preterm Infants. Issue 3 (September 2019) - Valentine, Christina J.; Dingess, Kelly A.; Kleiman, Jeanne; Morrow, Ardythe L.; Rogers, Lynette K.
Abstract : ABSTRACT: Maternal supplementation with 1000 mg/day docosahexaenoic acid (DHA) provides third trimester DHA accretion levels in breast milk for the preterm infant. We hypothesized that DHA supplementation to mothers providing breastmilk for extremely preterm infants would result in decreased inflammatory markers, in the infant. Mother/infant dyads (n = 27) were enrolled at birth and mothers were assigned to receive 200 or 1000 mg/day of DHA. Milk and plasma samples were analyzed for fatty acids and inflammatory markers. Decreases in inflammation were observed in both maternal and infant plasma and correlated with red blood cell (RBC) DHA levels. The fact that maternal DHA supplementation decreases infant markers of inflammation implies that DHA, delivered through breastmilk, has the potential to decrease inflammation in the infant. Abstract : Supplemental Digital Content is available in the text